2016
DOI: 10.1039/c6ra18017e
|View full text |Cite
|
Sign up to set email alerts
|

Illumina MiSeq sequencing reveals the community composition of NirS-Type and NirK-Type denitrifiers in Zhoucun reservoir – a large shallow eutrophic reservoir in northern China

Abstract: Denitrification is a major biological process that reduces nitrate to nitrogen gas (N2 or N2O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…Some unknown microorganisms maybe not are captured by the primers used in this study. In addition to nirS-type denitrifers, nirK-type denitrifer was observed in estuarine systems [12,38,39,40]. Although we have done some investigation about nirK gene in the PRE, the primers for nirK gene need to be optimized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some unknown microorganisms maybe not are captured by the primers used in this study. In addition to nirS-type denitrifers, nirK-type denitrifer was observed in estuarine systems [12,38,39,40]. Although we have done some investigation about nirK gene in the PRE, the primers for nirK gene need to be optimized.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, functional genes encoding nitrite reductase are characterized with more sequence changes, which can not only analyze the microbial community structure, but also identify the microbial communities' ecological functions. The functional genes of nirS and nirK have been proven to be credible molecular markers to reveal the community composition and structure of denitrifying microbes [12], which have been widely used to investigated the diversity of denitrifers in various environments, such as the aquatic ecosystems, sediments and also the wastewater treatment plant (WWTP) [13][14][15]. Previous studies showed that nirS-type denitrifers make up more than 70% of known denitrifiers [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redundancy analysis (RDA) was used to evaluate the relationship between the bacterial community structure and water environmental parameters with variance inflation factor analysis (VIF < 10) [ 29 , 30 ]. The mantel test was performed to investigate the relationships between water microbial/functional communities and environmental parameters [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the patterns of nirK diversity across soil groups were mirrored by the patterns of nos : nir, suggesting that changes in the size of the nirK community had a dominant influence on the overall ratio of complete and incomplete denitrifiers in soil groups. Independent shifts in nirS and nirK community structures in response to common physicochemical characteristics were recently observed in a eutrophic reservoir (Zhou et al, 2016). In contrast, the structure of nosZ communities did not correspond to any physicochemical property measured.…”
Section: Discussionmentioning
confidence: 99%